New macrocycles incorporating glycolipids via copper-catalyzed triazole coupling. Issue 1 (2nd January 2022) - Kareem, Nuha S.; Mohammed, Shaymaa A.; Abed, May Jaleel; Aneed, Asaad H.; Kamal, Hayder M.; Zahid, N. Idayu; Sabah, Karem J.
Abstract: A series of new macrocycles based on alkyl glycosides derived from D-glucose and D-galactose was synthesized. The macrocycles were easily obtained by the reaction of dialkynyl derivatives with diazides via copper-catlyzed 1, 3-cycloaddition reaction. Simple protecting group strategies were applied to obtain the vicinal dihydroxy derivatives, followed by Williamson etherification with propargyl bromides to get the dialkynyl derivatives. These derivatives were subjected to 1, 3-Hüisgen triazole coupling with diazides furnishing the macrocycles in good yields. The 1, 3-Hüisgen reaction used to build these macrocycles was investigated thoroughly with respect to reaction time, catalysts, solvents, and temperature for optimum macrocyclisation. Graphical Abstract: UF0001